Socialization of Innovation in Village View Case Regional Jember Law Court - Fina Rosalina; Lutfian Ubaidilah; Akbar Maulana (LPPM UIKA Bogor, 2023)
Simple, fast, and low-cost trials (Contante Justitie) are principles that must be fulfilled in the justice system. Often this principle is distorted due to the accumulation of cases in court. There is a renewable innovation for solving minor litigation cases in the jurisdiction of the Jember District Court, namely media services and information in applications. The innovation is called the Tilik Desa Application. The Tilik Desa program is a program that integrates judicial applications, service innovation, and information media in one application. One of the products of the Village View Application is light case services such as name changes or repairs which can be served through the village office where the case occurred. The purpose of this outreach is to disseminate information about the Village View Application and provide an understanding to the Jember Community about the Village View Application innovation. So that later the settlement of minor litigation cases, especially Applications for Change and Correction of Names, can be carried out simply, quickly, and at a low cost (Contante Justitie). This research concludes that, in addition to being able to realize the principles of simple, fast, and low cost (Contante Justitie), the Village View Program can minimize extortion at the level of village areas under the guise of being a service in completing small requests.